PENERAPAN METODE DRILL DALAM MENGHAFAL SURAH PENDEK PADA (Siswa Kelas IV SDN 7 Pelangsian Kecamatan Mentawa Baru Ketapang Kabupaten Kotawaringin Timur) - Rusyidah, Rusyidah (Jurnal Studi Agama dan Masyarakat, 2014)
Â The focus of this study originated from last years evaluation data , low ability students in SD Negeri 7 Pelangsian in memorizing short surahs that is classically only 35 % of the 26 students who were able to complete. This is due to the low ability of teachers to implement the method .This study uses classroom action research ( PTK ) is the research that implement recycling cycle in any research that includes studies of planning , implementation , observation and reflection . The results of this study turned out to be the effective application of the method drill on the competence memorize short verses are very precise . It can be seen the success rate of students in memorizing verses short , the application of methods drill there are few records to note that prior to the implementation of the exercise beforehand really conditioned the class , divide students into several parts group , and understanding the character of the students in the training processÂ